TRAPγ-CDG shows asymmetric glycosylation and an effect on processing of proteins required in higher organisms. Issue 3 (24th April 2020) - Dittner-Moormann, Sabine; Lourenco, Charles Marques; Reunert, Janine; Nishinakamura, Ryuichi; Tanaka, Satomi S; Werner, Claudius; Debus, Volker; Zimmer, Klaus-Peter; Wetzel, Gabriele; Naim, Hassan Y; Wada, Yoshinao; Rust, Stephan; et al.
Abstract : Newly synthesised glycoproteins enter the rough endoplasmic reticulum through a translocation pore. The translocon associated protein (TRAP) complex is located close to the pore. In a patient with a homozygous start codon variant in TRAPγ (SSR3), absence of TRAPγ causes disruption of the TRAP complex, impairs protein translocation into the endoplasmic reticulum and affects transport, for example, into the brush-border membrane. Furthermore, we observed an unbalanced non-occupancy of N-glycosylation sites. The major clinical features are intrauterine growth retardation, facial dysmorphism, congenital diarrhoea, failure to thrive, pulmonary disease and severe psychomotor disability.